2021
DOI: 10.1017/jfm.2020.993
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale coherent structures in compressible turbulent boundary layers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 61 publications
5
34
0
Order By: Relevance
“…alternating low- and high-speed streamwise structures of length greater than ) in the logarithmic region of an incompressible turbulent boundary layer, and these logarithmic structures have a modulating effect on the generation of small-scale near-wall motions. Superstructures have also been identified in supersonic adiabatic turbulent boundary layers using data from either PIV (Ganapathisubramani, Clemens & Dolling 2006; Bross, Scharnowski & Kähler 2021) or DNS (Ringuette, Wu & Martin 2008). Bernardini & Pirozzoli (2011 a ) further showed the occurrence of an inner–outer interaction and the importance of amplitude modulation imposed on the smaller-scale motions by the large-scale ones in DNS of a Mach 2 turbulent boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…alternating low- and high-speed streamwise structures of length greater than ) in the logarithmic region of an incompressible turbulent boundary layer, and these logarithmic structures have a modulating effect on the generation of small-scale near-wall motions. Superstructures have also been identified in supersonic adiabatic turbulent boundary layers using data from either PIV (Ganapathisubramani, Clemens & Dolling 2006; Bross, Scharnowski & Kähler 2021) or DNS (Ringuette, Wu & Martin 2008). Bernardini & Pirozzoli (2011 a ) further showed the occurrence of an inner–outer interaction and the importance of amplitude modulation imposed on the smaller-scale motions by the large-scale ones in DNS of a Mach 2 turbulent boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…2019; Li et al. 2021) and wall-bounded turbulence (Huang, Coleman & Bradshaw 1995; Pirozzoli & Bernardini 2011; Bross, Scharnowski & Kähler 2021; Xu et al. 2021 b ).…”
Section: Introductionmentioning
confidence: 99%
“…Bross et al. (2021) experimentally investigated compressibility effects on the large-scale coherent structures and their relation to turbulence statistics in compressible boundary layers. They found that compressibility has a clear effect on boundary layer, and that the scale of large-scale coherent structures based on the boundary layer thickness becomes longer and wider for supersonic turbulent boundary layers when compared with subsonic and transonic turbulent boundary layers.…”
Section: Introductionmentioning
confidence: 99%
“…This is most evident in high-speed, compressible flows (Williams 2014; Williams et al. 2018), but it has been observed at all Mach numbers (see, for example, Bross, Scharnowski & Kähler 2021). Recently, Aultman, Disotell & Duan (2022) used DNS to investigate the spatial resolution of PIV for the wall-normal components and clearly demonstrated the important role played by window size, and how spurious cross-correlations caused by the size of the illumination diameter and the local particle density set limits on the smallest acceptable window size.…”
Section: Future Directionsmentioning
confidence: 98%